New genus, new species and new record of Neanurinae (Collembola, Neanuridae) for the Neotropics - Queiroz, Gabriel C.; Deharveng, Louis (Zootaxa, 2015)
A new genus and a new species of Paleonurini (Collembola, Neanurinae) are described in this paper. The new species Ectonura snowdeni sp. nov., is the first record of the austral genus Ectonura for the Neotropics. A new genus from Southeast Brazil, Itanura gen. nov., is created based mainly on head tubercles arrangement. Its type species is Neanura brasiliensis Arlé, 1959 comb. nov., which is redescribed with the designation of a lectotype. Its distribution range is expanded with two new records from high altitude mountains of Southeast Brazil. Specimens from these two localities exhibit small morphological differences with those of the type locality, which are discussed.